The elements of library research : what every student needs to know - George, Mary W., 1948-2015. (Princeton, N.J. : Princeton University Press, 2008)
This short, practical book introduces students to the important components of the information-seeking process. Unlike guides that describe the research process but do not explain its logic, this book focuses entirely on basic concepts, strategies, tools, and tactics for research--in both electronic and print formats. --from publisher description
Introduction to research as inquiry -- From research assignment to research plan -- Strategy and tools for discovery -- The fine art of finding sources -- Insight, evaluation, argument, and beyond.
Includes bibliographical references (p. [191]-194) and index.
Keywords: Library research -- United States